Enhancing Purchase Decisions of Mie Sukses in Semarang through Brand Image and Brand Ambassador - Martini Martini; Firdaus Firdaus; Sri Sulistiyaningsih; Rusmiyatun Rusmiyatun; Fiderius Ismanto; Kukuh Mulyanto; Asepta Hendriyanto; Meizar Effendi; Alis Arifa Rahman; Wa Ode Sitti Nurrahmah; Muhammad Roby Jatmiko (Universitas Muhammadiyah Semarang, 2025)
This study aims to examine the influence of brand image and brand ambassador on purchase decisions of Mie Sukses in Semarang. The research problem is based on the question of how brand image and brand ambassador, both directly and indirectly, affect consumer purchasing behavior. A quantitative research design was applied with a structured questionnaire distributed to 144 consumers of Mie Sukses who were selected using purposive sampling, ensuring that respondents had purchased the product at least twice in the past three months. The collected data were analyzed using structural equation modeling to test the relationships between the studied variables. The results reveal that brand image has a strong positive effect on purchase decision, confirming its role as the most important factor in shaping consumer behavior. Meanwhile, brand ambassador shows a significant but negative effect on purchase decision, indicating a possible mismatch between the ambassador’s credibility and consumer expectations. Furthermore, brand image significantly affects brand ambassador, while the indirect effect of brand image on purchase decision through brand ambassador is negative. These findings highlight the dominant role of brand image and the importance of aligning ambassador selection with target consumer perceptions.